DigitalPinDirector: A digital pinscreen editor for images and realtime animation in low cost personal computers - Lochon, A.; Lopes, P. F.; Dias, M. (SIGraDi 2011 Proceedings of the 15th Iberoamerican Congress of Digital Graphics, 2011)
This paper presents the main characteristics of the traditional Pinscreen, the way it works, its problems and results achieved. The first Digital Pinscreen system is presented, along with its main characteristics and limitations. The rest of the paper describes and presents the DigitalPinDirector: a system that enables a full and true creative access to the unique visual and animation characteristics of the Pinscreen.